Explorative study on patterns of game structure in male and female matches from elite Spanish soccer - Tenga, A.; Zubillaga, A.; Caro, O.; Fradua, L. (International Journal of Performance Analysis in Sport, 2015)
The aim of this study was to explore emergent patterns of game structure in male and female matches from elite soccer by using playing distances measured according to the ball location. Archive data based on carefully selected four male and four female matches from elite Spanish soccer seasons 2002-3, 2003-4 and 2004-5 were collected by help of AMISCO PRO® system. Differences across six ball locations were found in mean playing length (÷2 5=328.1 and 520.9, P<0.001) and playing width (÷2 5=39.6 and 26.9, P<0.001) from male and female matches, respectively. Both sexes displayed similar movements in playing length that vary with stretchcontraction- stretch patterns and in playing width that vary with opposite patterns of contraction-stretch-contraction, but these patterns varied to a significantly greater extent in male matches. For example, male matches (mean=44.93±8.34 m) produced significantly (U=128564.0, z=-8.2, P<0.001) longer playing width during transition phase in midfield compared with female matches (mean=41.80±8.00 m). Results suggest that female matches produced less favourable patterns of game structure with fewer penetration opportunities than male matches. Specific suggestions for coaching intervention were given. This study demonstrates the potential of analysing playing distances according to the ball location for studying patterns of game structure in real soccer matches.